2020
DOI: 10.5935/2595-0118.20200187
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effect of two virtual reality stimuli on pressure pain sensitivity and autonomic response

Abstract: BACKGROUND AND OBJECTIVES: Inflammation is a defense response of the body to a cellular damage caused by physical, chemical or biological agents, which triggers, among other factors, pain. Although inflammation plays an important role in the protection and regeneration of tissue injury, inflammatory pain results in decreased quality of life. In view of this, the development of safe and less invasive forms for the treatment of inflammatory pain is of great importance. The objective of this study was to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Eight articles showed signi cant effectiveness of VR in reducing the pain level and time spent thinking about pain in patients suffering labor-related pain, burn wound care, dental procedures, and postoperative wound dressing change [30]. Other studies have demonstrated that subjects using VR equipment were more tolerant to painful thermal, electrical, and pressure stimuli compared to those who didn't receive VR headsets [31,32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Eight articles showed signi cant effectiveness of VR in reducing the pain level and time spent thinking about pain in patients suffering labor-related pain, burn wound care, dental procedures, and postoperative wound dressing change [30]. Other studies have demonstrated that subjects using VR equipment were more tolerant to painful thermal, electrical, and pressure stimuli compared to those who didn't receive VR headsets [31,32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that painful stimuli like IVC insertion can cause an autonomic nervous system response that increases a patient's heart rate (HR) [ 22 , 23 ]. Therefore, some clinicians use HR to evaluate pain in their patients.…”
Section: Discussionmentioning
confidence: 99%
“…That is, emotional regulation in the presence of an attentive task involves a network composed of the lateral prefrontal cortices, temporal and parietal regions, as well as the supplementary motor area and the cingulate cortex. 21 Gold et al explored further on this neurobiology of virtual reality pain attenuation. They stated that immersive VR diverted attention from an unpleasant setting such as pain to a pleasant and absorbing virtual world while engaging higher cognitive and emotional centers of the nervous system, in this way VR can markedly diminish a patient's subjective pain experience.…”
Section: Distraction/diversion Of Attentionmentioning
confidence: 99%